Pemanfaatan Teknologi Informasi dan Kinerja Individual(Survei Pada Karyawan Rumah Sakit PKU Muhammadiyah Surakarta) - Purnama, Septian, Dr. Erma Setiawati, MM.,CA (2017)
The aim of this study is to obtain the evidence concerning information technology uses. This paper draws factors that influence information technology uses such as social factor, affect, complexity, job-fit, long-term consequences, facilitating condition; and individual performance in the hospital. The research method used is purposive sampling method to 35 hospital employees (finance) shared on the hospital of PKU Muhammadiyah Surakarta. The Structural Equation Model analysis is used to test the hypothesis. The hypothesis test proved that affect, facilitating condition have significantly correlated to information technology uses. Nevertheless, social factor, complexity, job-fit, long-term consequences have not significantly correlated to information technology use. Finally, the last hypothesis test proved that information technology uses was positively and significantly to individual performance as well